Does postcholecystectomy increase the risk of colorectal cancer? - Dong, Zhenyu; Shi, Ruixian; Li, Pengda; Song, Xiaobiao; Dong, Fan; Zhu, Jianmin; Wu, Riga; Liang, Zhi; Du, Mingyue; Wang, Jijun; Yang, Zhigang (Frontiers in Microbiology, 2023)
With the increasing number of cholecystectomy and the high proportion of colorectal cancer in malignant tumors, the question whether cholecystectomy is a risk factor for colorectal disease has been widely concerned. After reviewing the literature at home and abroad, the author will summarize the research progress of the correlation between the occurrence of colorectal tumors after cholecystectomy, in order to provide help for the prevention and treatment of colorectal tumors.